Technical Efficiency and the Factors that Affect it in Rice Production in Indonesia - Muhardi; Effendy (Asian Journal of Agriculture and Rural Development, 2021)
Most of the population of Asia depends on consuming rice to support their lives. This implies that rice production needs attention. The existence of inefficiencies in lowland rice production could reduce rice yields for consumption, so the measurement of technical efficiency in lowland rice production needed to be studied. This research aimed to analyze the level of technical efficiency in lowland rice cultivation and identify the factors affecting it. The research was done in the Palolo and Torue subdistrict of Indonesia. The number of samples used was 249 lowland rice farmlands, consisting of 106 and 143 farmers of organic and inorganic lowland rice cultivation, respectively. The results show that land, fertilizer, seeds, and labor had a positive and significant effect on lowland rice production. The average technical efficiency of lowland rice cultivation was around 78.2%. The results also show that manager education, extension contacts, superior seeds, and organic lowland rice cultivation have a significant effect on the level of technical efficiency in lowland rice production. We concluded that there is an opportunity for farmers to increase lowland rice yields if they can manage production factors in an efficient manner. The government could provide support for farmers, such as formal and informal education, extension, superior seeds, and ready-to-use organic materials.